Formação continuada de professores no contexto da educação inclusiva - Sponchiado, Laercio Francisco (2020)
This research aims to investigate whether continuing teacher education is enabling teachers to work with students who have disabilities, global developmental disorders and high skills or giftedness. For this, we sought to situate the researcher's personal and professional life trajectory, as well as his imbrication with the theme. In other words, research on the theme sprang from the family life of having someone with a learning disability, which makes us see and review the disabled student in his relationship with the school and the teacher. Therefore, a personal experience, as a father, that influenced doing and acting professionally as a teacher, leading to concern with the issue of including students with disabilities in the school environment. As a methodology for its development, we use bibliographic, documentary and field research. The bibliographic review was based on the production carried out on the theme from 2014 to 2018, especially in the articles published by SciELO and Anped. We also seek other conceptions of inclusive education and teacher training in Mantoan (2003; 2011); Mantoan; Prieto and Arantes (2006); Jannuzzi (1992; 2004); Mazzotta (1982; 1996); Freire (1980; 1987; 1991; 2011); Libâneo (2017); Nóvoa (2019); Nóvoa and Vieira (2017); Vasconcellos (2011); Pacheco (2007); Sartori (2013) and others. As for documentary research, we look especially in cursive records, which are documents prepared by government agencies, such as the Brazilian Education Guidelines and Bases Laws (1961, 1971 and 1996); the 1988 Federal Constitution; the National Special Education Policy from the perspective of Inclusive Education (2008); the 10-year Education Plans (2001-2010 and 2014-2024). And yet, the World Education Declarations, such as the World Declaration on Education for All (Jomtien Declaration, 1990); the Salamanca Declaration (1994) and the Buenos Aires Declaration (2017). Regarding the methodological assumptions, we used the qualitative approach in the search for understanding the proposed theme, based on Minayo (1994), Gatti (2005); Gil (2010; 2002) and Gaskell (2008). As an integral part of the research methodology, we used a research instrument known as a focus group, understanding that it would contribute more significantly to the research process. Finally, this research has as its final objective the availability of a training proposal around the theme of Continuing Education for teachers: from speech to practice in inclusion, for the teachers of the researched school, thus fulfilling the requirement of the Professional Master in Education, which is making a product available.